Single minute exchange of dies with fuzzy-analytic hierarchy process method for setup time reduction : an application in advanced composite manufacturing industry
For many decades, extensive attention has been given to the action of reducing the setup time and most of them are practicing the Single Minute Exchange of Dies (SMED), developed by Shigeo Shingo in 1960s. However, the four phases recommended by Shingo in his SMED is not the optimal solution for setup time reduction in all circumstances. Selecting the most suitable decisions during SMED implementation require deep thought and thorough consideration of all possible solutions. Hence, this research study endeavored to develop an improved methodology to solve setup time reduction problem by integrating Single Minute Exchange of Dies (SMED) with Fuzzy-Analytical Hierarchy Process (Fuzzy-AHP). In this research study, the validation of the proposed sequential phases methodology was done in actual industrial working environment. The industrial case study was divided into three individual case studies. The Fuzzy-AHP method benefited in the selection of the best improvement solution for each case study. As the outcome from the SMED-FAHP implementation, the setup time for 5-axis trimming machine along with the Drilling Router Jig (DRJ) and composite panel management for Product X has been reduced. In Case Study 1, all of the internal setup activities are transferred into external activities which can be performed without the stoppage of the trimming machine. Meanwhile, in Case Study 2, 91.2% of internal setup time has been reduced. In Case study 3, 64.1% of internal setup time has been successfully reduced after the implementation of chosen improvement solution. The result proved the effectiveness of the SMED-FAHP method in reducing setup time for 5-axis trimming machine in composite manufacturing industry.